Identification of Escherichia coli in PDAM Drinking Water of Kladufu District, Sorong City - Fenti A Tupanwael; Junaiddin; Andirwana; Evi Hudriyah Hukom; Diva Dallas Soulisa (UNIVERSITAS KHAIRUN, 2026)
Escherichia coli is a Gram-negative bacterium that causes intestinal and extraintestinal diseases in humans due to the consumption of unhygienic beverages. Its virulence allows Escherichia coli to evade the host's immune system. This study aims to identify the presence of Escherichia coli bacteria in PDAM drinking water consumed by residents of RT 010 RW 002 Kladufu Village, Sorong City. This study uses a descriptive method with a laboratory observation approach and a cross-sectional research design. The population in this study consists of all households that consume PDAM drinking water without boiling it, totaling 60 homes. The sampling technique is purposive sampling, considering the established inclusion and exclusion criteria. Out of 60 research samples, only 38 were willing to be respondents and met the criteria, resulting in 38 water samples for laboratory testing. The research results show that out of 38 water samples tested, 20 samples (57.9%) were identified as positive for Escherichia coli bacteria, and 18 samples (42.1%) did not contain these bacteria. This finding indicates that most of the PDAM water consumed by residents has not yet met the standards for safe drinking water quality, which could pose a health risk.